Síntese e caracterização de aluminas micro e nanoparticuladas dopadas com carbono (AI2O3:C) para aplicação em dosimetria das radiações - Crissia Carem Paiva Pinto (2010)
Al2O3 crystals doped with carbon have been considered excellent materials for ionizing radiation dosimetry purposes, in view of their luminescent properties. As much the photostimulated as the thermostimulated phosphorescence properties make Al2O3:C one of the best dosemeters in use in the world, nowadays. A small number of researchers own the knowledge of how to produce these carbon-doped aluminum oxides. The secret resides in the grade and in the way of doping with carbon. In this work, nano and micro-sized alumina doped with different percentages of carbon, sintered under different atmosphere conditions, at temperatures ranging from 1300°C to 1750°C, were investigated. All the produced samples were gamma irradiated. The emitted photoluminescent signals (OSL) were analyzed by a spectrometer in the range of 190nm to 900nm. Samples were excited by monochromatic light ranging from 250nm to 700nm using a system with Deuterium and Tungsten lamps coupled to a monochromator. Thermoluminescent signals (TL) were registered by a TL Reader, after heating the samples from 25°C to 330°C, with heating rates varying from 1,0°C.s-1 to 10°C.s-1 Both nano and micro-sized alumina have not shown any significant OSL signal, for the doping and sintering temperatures studied here. On the other hand, the investigation about the TL properties has revealed that the nano-sized alumina shown TL output lower than those reported in the literature. However, the micro-sized samples have shown an excellent TL sensitivity, comparable to the best TL sensitivities ever reported to alumina. Among the investigated sample preparation methods, the micro-sized alumina doped with 0.01% of carbon and sintered at 1700°C under reducing atmosphere has presented the best TL output. The study of its dosimetric properties has revealed a TL response 50,8 times the response of LiF:Mg,Ti, when exposed to 10mGy. The main TL emission peak is situated around 240°C and it can be decomposed into two individual peaks at 219°C and 244°C, respectively, for a heating rate of 10°C.s-1 during the reading process. The Fading studies indicate that when the irradiated samples are stored under visible light the loss of signal is about 96% and, when stored in the dark, there is an increase in the TL signal that can reach until 40%. The influence of humidity in the TL signal has been evaluated to be -4,0% for low humidity conditions and insignificant for high humidity conditions. The investigation of the dependence of TL output with the energy of the photon beams has revealed that the TL response for photons with effective energy of 48keV is 3,0 times the relative response for gamma photons. Finally, comparing all these results with the literature we conclude that the synthesis under reducing conditions at 1700°C for Al2O3 crystals doped with 0.01% of carbon produces a TL material with thermoluminescent properties quite similar to the best alumina dosemeters produced by patented methodologies in the world. Thus, we can say that the micro-sized alumina obtained by the methodology used in this work is a good candidate for application in X and Gamma radiation dosimetry.